تحسين كفاءة نظم القدرة الشمسية الكهروضوئية باستخدام متحكم تتبع نقطة الاستطاعة العظمى المرتكز على مبدل رافع للجهد المستمر - ديلانة إيمان (Latakia University Journal -Engineering Sciences Series, 2017)
يعالج هذا البحث تحسين كفاءة نظم القدرة الشمسية الكهروضوئية باستخدام متحكم تتبع نقطة الاستطاعة العظمى، المرتكز في عمله على تقنيات تتبع تستخدم طريقة التحكم المباشر للتحكم في دورة عمل مبدل جهد مستمر لتحقيق عمل النظام الكهروضوئي عند نقطة الاستطاعة العظمى في ظل التغيرات الجوية المختلفة من شدة إشعاع شمسي ودرجة حرارة محيطة. في هذا السياق، يتركز عملنا على محاكاة مكونات نظام توليد الطاقة من نظام كهروضوئي، مبدل رافع للجهد المستمر ومتحكم MPPT في بيئة Matlab/Simulink. تتم محاكاة المتحكم MPPT باعتماد عدة خوارزميات: خوارزمية التوتر الثابت، خوارزمية الإضطراب والمراقبة وخوارزمية زيادة الناقلية، باستخدام تابع Embedded MATLAB function. أظهرت نتائج المحاكاة فعالية المتحكم MPPT في زيادة استطاعة النظام الكهروضوئي مقارنة مع عدم استخدام متحكم MPPT. كما أظهرت النتائج الأداء الأفضل لمتحكم MPPT المعتمد على خوارزمية الإضطراب والمراقبة وخوارزمية زيادة الناقلية، مقارنة مع خوارزمية التوتر الثابت في تتبع نقطة الاستطاعة العظمى للنظام في ظل التغيرات الجوية. This research deals with improving the efficiency of solar photovoltaic (PV) power systems using a Maximum Power Point Tracker controller (MPPT controller), based in his work on the Maximum Power Point Tracking techniques via the direct control method. Which used to control the duty cycle of DC-DC Voltage Converter, to achieve the photovoltaic system works at a Maximum Power Point under different atmospheric changes of the solar insolation and ambient temperature. In this context, our work is focused on the simulation of the components of the power generating system, such as the photovoltaic system, DC-DC Boost Converter and a MPPT controller in Matlab/Simulink environment. The simulating of the MPPT controller was based on several algorithms such as: Constant Voltage algorithm, Perturb and Observe algorithm and Incremental Conductance algorithm by using Embedded MATLAB function. The simulation results showed the effectiveness of the MPPT controller to increase the photovoltaic system power compared with non-use of a MPPT controller. The results also showed the best performance of MPPT controller based on Perturb and Observe and Incremental Conductance algorithm, compared with constant voltage algorithm in tracking the Maximum Power Point under atmospheric changes.